2002
DOI: 10.1111/j.1095-8649.2002.tb01710.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of sodium bicarbonate on the motility of sperm of Japanese eel

Abstract: Sperm motility of Japanese eel Anguilla japonica was depressed from 59·1 to 1·1% when NaHCO 3 concentration increased from 0 to 150 m. In 25 m NaHCO 3 , when pH of the medium was 6·2, 7·2, 8·2, 9·2 and 10·2, relative sperm motility was 0, 0, 55·8, 93·7 and 136·6%, respectively to that of the control (0 m NaHCO 3 ). The remarkable effect in acid or neutral condition indicates that free-CO 2 (liberated CO 2 and H 2 CO 3 ) is a key factor for the motility inhibiting effect of NaHCO 3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In a previous study, the authors of the present study reported the inhibitory effect of NaHCO 3 on the initiation of sperm motility in the Japanese eel Anguilla japonica and applied the result to sperm preservation. 8,12 The next step was to find out the role of NaHCO 3 in order to improve the motility of the preserved sperm. In marine teleosts, [pH] i , [K + ] i and [Ca 2+ ] i have been reported as internal factors for the initiation of sperm motility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, the authors of the present study reported the inhibitory effect of NaHCO 3 on the initiation of sperm motility in the Japanese eel Anguilla japonica and applied the result to sperm preservation. 8,12 The next step was to find out the role of NaHCO 3 in order to improve the motility of the preserved sperm. In marine teleosts, [pH] i , [K + ] i and [Ca 2+ ] i have been reported as internal factors for the initiation of sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of sperm motility was carried out as reported in the study by Tanaka et al . 12 The following solutions were prepared for the experiments: NaCl, potassium chloride (KCl), CH 3 COONa, CaCl 2 , 2-morpholinoethane-sulfonic acid monohydrate (MES), 2-[4-(2-hydroxyethyl)-1-piperazinyl]ethane-sulfonic acid (HEPES) and TAPS (all from Wako Pure Chemical Industries, Osaka, Japan); NaHCO 3 and NH 4 Cl (Katayama Chemical Industries, Osaka, Japan); and 4-AP (Sigma Chemical Co., St. Louis, MO, USA). Distilled water was used for the dissolution of all reagents.…”
Section: Sperm Samples: Quantification Of Motility and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…New experiments are required using dilution factors as low as 1:1 or 1:2, allowing the maintenance of high concentrated sperm samples in the 250 ll straws. On the other hand, sodium bicarbonate concentrations as high as 75 mM seem to be a critical point, due to its role in controlling the initiation of spermatozoa motility, as has been proven in the Japanese eel (Tanaka et al 2002a(Tanaka et al , 2002b2004).…”
Section: As Wellmentioning
confidence: 93%
“…In the present study, we will compare the P1 medium (Asturiano et al 2004) and the medium described above (Tanaka et al 2002a). Tanaka et al (2002b) suggested that NaHCO 3 has an inhibitory role on the movement of the Japanese eel sperm, as to trigger the initiation of movement is necessary the influx of H + in the cell, and NaHCO 3 decreases intracellular pH. This decrease in the intracellular pH is produced because intracellular CO 2 (derived from NaHCO 3 ) is converted in HCO À 3 and H + by carbonic anhydrase.…”
Section: Introductionmentioning
confidence: 99%